Pharmacokinetic Study of Levetiracetam in Children - Pellock, John M.; Glauser, Tracy A.; Bebin, E. Martina; Fountain, Nathan B.; Ritter, Frank J.; Coupez, René M.; Shields, W. Donald (Epilepsia (Copenhagen), 2001)
Purpose: The pharmacokinetics of the novel antiepileptic drug (AED) levetiracetam and its major metabolite, ucb L057, were studied in children with partial seizures in a multicenter, open‐label, single‐dose study. Methods: Twenty‐four children (15 boys, nine girls), 6 to 12 years old, received a single dose of levetiracetam (20 mg/kg) as an adjunct to their stable regimen of a single concomitant AED, followed by a 24‐h pharmacokinetic evaluation. Results: In children, the half‐lives of levetiracetam and its metabolite ucb L057 were 6.0 ± 1.1 and 8.1 ± 2.7 hours, respectively. The Cmax and area under the curve (AUC) of levetiracetam equated for a 1‐mg/kg dose were lower in children (Cmax, norm = 1.33 ± 0.35 μg/ml; AUCnorm = 12.4 ± 3.5 μg/h/ml) than in adults (Cmax, norm = 1.38 ± 0.05 μg/ml; AUCnorm = 11.48 ± 0.63 μg/h/ml), whereas the renal clearance was higher. The apparent body clearance (1.43 ± 0.36 ml/min/kg) was ∼30–40% higher in children than in adults. Levetiracetam was generally well tolerated. Conclusions: On the basis of these data, a daily maintenance dose equivalent to 130–140% of the usual daily adult maintenance dosage (1,000–3,000 mg/day) in two divided doses, on a weight‐normalized level (mg/kg/day) is initially recommended. Clinical efficacy trials in children are ongoing with dosages of 20 to 60 mg/kg/day.